Knocked-Out Bombyx mori Protein Disulfide Isomerase Decreases Silk Yields and Mechanical Properties by Affecting the Post-Translational Modification of Silk Proteins - Shifeng Yang; Mengyao He; Xian Li; Huan Dong; Hexu Lei; Fangyu Wang; Hanxin Deng; Hongji Zhou; Siyu Chen; Yujuan Zhou; Zihan Meng; Ding Tu; et al. (Insects)
Silkworms synthesize and secrete silk to produce cocoons, which are excellent materials for textile and biomaterial manufacturing applications. However, the gene regulation associated with the post-translational modification of silk proteins remains unknown. In this study, we analyzed the physicochemical properties, evolutionary relationships, and expression patterns of BmPDI in silkworms. Subsequently, we knocked out BmPDI (BmPDI-KO), resulting in significant phenotypes of BmPDI-KO silkworms with smaller silk glands and cocoons, weaker silk mechanical properties, and reduced disulfide bonds in silk-associated proteins. Transcription levels of silk protein-related genes and unfolded protein response signal pathway-related genes were significantly downregulated. In contrast, genes involved in the apoptosis pathway were significantly upregulated in BmPDI-KO silkworms. Knocking out BmPDI in silkworms affected the post-translational modifications of the silk proteins, thereby accumulating misfolded silk proteins and hindering their secretion into the extracellular cells. This further increased endoplasmic reticulum stress, activated the apoptotic pathway, accelerated silk gland cell apoptosis, and significantly reduced the silk yields and mechanical properties of BmPDI-KO silkworm. This study provides a potential exploration of BmPDI in the modification of silk yields and mechanical properties of Bombyx mori.